2001
DOI: 10.1002/ajim.10024
|View full text |Cite
|
Sign up to set email alerts
|

Test‐retest reliability of the Upper Extremity Questionnaire among keyboard operators*†

Abstract: Reliability of items on the Upper Extremity Questionnaire were generally good to excellent. Reports of symptom severity and interference with work were less stable. Demographic and work-related factors were not statistically significant in modeling the variation in reliability. Repeated use of the questionnaire with similar results suggests findings are applicable to a larger working population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…All scales of the OAB-q exceeded this standard, with ICCs ranging from 0.83 to 0.95. These values are roughly equivalent or superior to ICCs reported for 7-day micturition diaries [Brown et al, 2003] and other patientreported outcome instruments designed for a range of medical conditions [Terwee et al, 1999;Salerno et al, 2001].…”
Section: Discussionsupporting
confidence: 53%
“…All scales of the OAB-q exceeded this standard, with ICCs ranging from 0.83 to 0.95. These values are roughly equivalent or superior to ICCs reported for 7-day micturition diaries [Brown et al, 2003] and other patientreported outcome instruments designed for a range of medical conditions [Terwee et al, 1999;Salerno et al, 2001].…”
Section: Discussionsupporting
confidence: 53%
“…The questionnaire incorporated items from previous research on upper extremity disorders, including items previously shown to have good to excellent test-retest reliability [19,24,[28][29][30][31][32]. Follow-up questionnaires with similar questions to the baseline questionnaire were completed at approximately 6 months, 18 months, and 36 months after baseline testing.…”
Section: Methodsmentioning
confidence: 99%
“…A frequently mentioned problem with test-retest studies is that the items being studied changed between testing periods (Fagarasanu and Kumar, 2002;Kerlinger and Howard, 1992;Salerno et al, 2001). In the current study, most of the groups completed their second round between three and five months after completion of the initial round.…”
Section: Study Strengthsmentioning
confidence: 98%
“…One of the limitations of this and other repeatability studies is the impact of a participant's memories (Salerno et al, 2001). Some subjects may have been able to remember during the second round how they scored job files from the first round.…”
Section: Study Limitationsmentioning
confidence: 98%